An Inhibitor of NF-κB and an Agonist of AMPK: Network Prediction and Multi-Omics Integration to Derive Signaling Pathways for Acteoside Against Alzheimer’s Disease - Li, Ying-Qi; Chen, Yi; Jiang, Si-Qi; Shi, Yuan-Yuan; Jiang, Xiao-Li; Wu, Shan-Shan; Zhou, Ping; Wang, Hui-Ying; Li, Ping; Li, Fei (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer’s disease (AD) is the most frequent type of dementia. Acteoside (ACT) is a compound isolated from Cistanche tubulosa, which possesses excellent neuroprotective properties. However, the underlying mechanism of ACT in regulating microglia polarization remains ill-defined. Therefore, a computational network model was established to identify the driving targets of ACT and predict its mechanism by integrating multiple available databases. The AlCl3-induced AD model in zebrafish larvae was successfully constituted to demonstrate the therapeutic efficacy of ACT. Subsequently, LPS-induced BV-2 cells uncovered the positive role of ACT in M1/M2 polarization. The NF-κB and AMPK pathways were further confirmed by transcriptomic analysis, metabolomics analysis, molecular biology techniques, and molecular docking. The research provided an infusive mechanism of ACT and revealed the connection between metabolism and microglia polarization from the perspective of mitochondrial function. More importantly, it provided a systematic and comprehensive approach for the discovery of drug targets, including the changes in genes, metabolites, and proteins.